2008
DOI: 10.1007/s00192-008-0626-7
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal tape lysis for urinary obstruction after suburethral tape placement. When to do an immediate replacement?

Abstract: To evaluate the interest and the indications of an immediate replacement of a suburethral tape after tape lysis for urinary obstruction is the aim of the study. From 2000 until 2007, a total of 22 patients underwent suburethral tape placement for stress urinary incontinence and developed thereafter a bladder outlet obstruction. These patients had a transvaginal tape lysis under local anesthesia. An immediate replacement of the tape was carried out in those patients who developed leakage under cough provocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Urethrolysis. Case series show improved voiding and lower PVR volumes, improvement or resolution of symptoms and QoL, and improvement of urodynamic parameters after urethrolysis treatment [82][83][84]. De novo SUI was reported in 39% of cases in one study [84].…”
Section: 2237mentioning
confidence: 90%
“…Urethrolysis. Case series show improved voiding and lower PVR volumes, improvement or resolution of symptoms and QoL, and improvement of urodynamic parameters after urethrolysis treatment [82][83][84]. De novo SUI was reported in 39% of cases in one study [84].…”
Section: 2237mentioning
confidence: 90%
“…Overall, 23 [14][15][16][17][18][19][20][21][22][23][25][26][27][30][31][32]36,[38][39][40][41]47,48 singlegroup studies that evaluated partial mesh removal, four 3,44-46 single-group studies that looked at total mesh removal, and four comparative studies support an association between improvement in lower urinary tract symptoms after surgery, regardless of mesh removal amount.…”
Section: Resultsmentioning
confidence: 99%
“…Of the four patients with persistent bladder outlet obstruction, mesh sling transection was performed 4-8 months later with 100% resolution. Comparative and single-group studies 3,14,17,19,20,23,[26][27][28][29][30][31][32]39,41,[43][44][45]52,54 demonstrated no difference in bladder outlet obstruction outcomes between total and partial mesh excision; both techniques showed an associated improvement in bladder outlet obstruction symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation